Sect, Subsidy, and Sacrifice: An Economist's View of Ultra-Orthodox Jews* - Berman, Eli (Quarterly Journal of Economics, 2000)
Israeli Ultra-Orthodox men study full-time in yeshiva until age 40 on average. Why do fathers with families in poverty choose yeshiva over work? Draft deferments subsidize yeshiva attendance, yet attendance typically continues long after exemption. Fertility rates are high (TFR = 7.6) and rising. A social interaction approach explains these anomalies. Yeshiva attendance signals commitment to the community, which provides mutual insurance to members. Prohibitions strengthen communities by effectively taxing real wages, inducing high fertility. Historically, the incursion of markets into traditional communities produces Ultra-Orthodoxy. Subsidies induce dramatic reductions in labor supply and unparalleled increases in fertility, illustrating extreme responses social groups may have to interventions.